2022
DOI: 10.1371/journal.pntd.0010241
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme immunoassays (EIA) for serodiagnosis of human leptospirosis: specific IgG3/IgG1 isotyping may further inform diagnosis of acute disease

Abstract: The laborious microscopic agglutination test (MAT) is the gold standard serologic test for laboratory diagnosis of leptospirosis. We developed EIA based serologic assays using recombinant proteins (rLigA, rLigB, rLipL32) and whole-cell extracts from eight Leptospira serovars as antigen and assessed the diagnostic performance of the new assay within each class, against MAT positive (MAT+) human sera panels from Portugal/PT (n = 143) and Angola/AO (n = 100). We found that a combination of recombinant proteins rL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Our previous studies showed innate immunity engagement during saprophytic L. biflexa infection (14, 15). In addition, L. biflexa extracts can be used to detect Leptospira -specific antibody in up to 67% of serum from patients with clinically confirmed leptospirosis (18) which points to a high degree of immunodominant cross-reactive epitopes between L. biflexa and pathogenic Leptospira . Thus, we hypothesized that these highly cross-reactive immunodominant epitopes may also induce cross-protective immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed innate immunity engagement during saprophytic L. biflexa infection (14, 15). In addition, L. biflexa extracts can be used to detect Leptospira -specific antibody in up to 67% of serum from patients with clinically confirmed leptospirosis (18) which points to a high degree of immunodominant cross-reactive epitopes between L. biflexa and pathogenic Leptospira . Thus, we hypothesized that these highly cross-reactive immunodominant epitopes may also induce cross-protective immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…rRNA primers (Forward-CCCGCGTCCGATTAG and Reverse-TCCATTGTGGCCGAACAC) and TAMRA probe (CTCACCAAGGCGACGATCGGTAGC) were used for Leptospira detection using qPCR with a standard curve of 10 5 to 1 Leptospira (16,17). Similarly, qPCR was performed with kidney tissues placed in EMJH to grow live Leptospira after culturing for 5 days and visually quantified under a dark field microscope (20X, Zeiss USA, Hawthorne) on d3 and d5 post culture inoculation.…”
Section: Leptospira 16smentioning
confidence: 99%
“…Given that IgM/IgD class and IgG3/ IgG1-specific isotypes are produced in the earliest course of infection, immunoglobulin G isotyping may be used in the diagnosis of acute leptospirosis. EIA tests with its speed, ease of use, and accuracy make them good alternatives to the laborious MAT [74].…”
Section: Recent Advances In Investigationsmentioning
confidence: 99%
“…The advantages of this method are the selection of a specific biomatrix for testing (in contrast with the determination of viruses or bacteria in different organs and tissues), and the similarity of the assay protocols for various infections [ 1 ]. In medical diagnostics, microplate-based enzyme-linked immunosorbent assays (ELISAs), agglutination tests, and other immunoassay formats are successfully used for this purpose [ 2 , 3 , 4 ]. The current trend in the development of diagnostic tools is simplification and acceleration of the testing procedure.…”
Section: Introductionmentioning
confidence: 99%